2020
DOI: 10.3390/ijms21218259
|View full text |Cite
|
Sign up to set email alerts
|

Target of Rapamycin in Control of Autophagy: Puppet Master and Signal Integrator

Abstract: The target of rapamycin (TOR) is an evolutionarily-conserved serine/threonine kinase that senses and integrates signals from the environment to coordinate developmental and metabolic processes. TOR senses nutrients, hormones, metabolites, and stress signals to promote cell and organ growth when conditions are favorable. However, TOR is inhibited when conditions are unfavorable, promoting catabolic processes such as autophagy. Autophagy is a macromolecular degradation pathway by which cells degrade and recycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 243 publications
(333 reference statements)
0
29
0
Order By: Relevance
“…Despite the increasing evidence linking the TORC pathway to the integration of metabolic signals, energy status, and hormones in a wide range of plant growth-mediated processes ( Moreau et al, 2012 ; Caldana et al, 2013 ; Xiong et al, 2013 ; Pfeiffer et al, 2016 ; Zhang et al, 2016 ; Dong et al, 2017 ; Li et al, 2017 ; Mohammed et al, 2018 ; Salem et al, 2018 ), little is known about its mode of action and the key players in controlling cellular homeostasis in a condition-dependent manner. The downregulation of TORC in plants activates autophagy, which derives from the generation of autophagosomes, enhanced expression of ATG genes, and their phosphorylation [reviewed by Mugume et al (2020) ], aside from nucleotides depletion ( Kazibwe et al, 2020 ). The role of TOR as a repressor of autophagy ( Pu et al, 2017 ), this process suggested to generate proteogenic dipeptides ( Thirumalaikumar et al, 2020 ), makes raptor1b a suitable model to study the regulatory interplay among light, C availability, TOR, and small molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing evidence linking the TORC pathway to the integration of metabolic signals, energy status, and hormones in a wide range of plant growth-mediated processes ( Moreau et al, 2012 ; Caldana et al, 2013 ; Xiong et al, 2013 ; Pfeiffer et al, 2016 ; Zhang et al, 2016 ; Dong et al, 2017 ; Li et al, 2017 ; Mohammed et al, 2018 ; Salem et al, 2018 ), little is known about its mode of action and the key players in controlling cellular homeostasis in a condition-dependent manner. The downregulation of TORC in plants activates autophagy, which derives from the generation of autophagosomes, enhanced expression of ATG genes, and their phosphorylation [reviewed by Mugume et al (2020) ], aside from nucleotides depletion ( Kazibwe et al, 2020 ). The role of TOR as a repressor of autophagy ( Pu et al, 2017 ), this process suggested to generate proteogenic dipeptides ( Thirumalaikumar et al, 2020 ), makes raptor1b a suitable model to study the regulatory interplay among light, C availability, TOR, and small molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to translation, mTORC1 is a negative regulator of autophagy, which is an intracellular process that allows orderly degradation and recycling of cellular components, including amino acids. Autophagy is regulated by mTORC1 through its phosphorylation of UNC-51-like kinase 1 (ULK) (196)(197)(198)(199)(200). Therefore, mTORC1 signaling plays a role in AA deprivation adaptation by limiting protein translation and increasing amino acid pools through autophagy (Figure 6).…”
Section: Activation Of the Amino Acid Response Pathway (Aar) Can Lead To Nutrient Stress Resistancementioning
confidence: 99%
“…Two putative homologs of LST8, LST8-1 and LST8-2, have been identified in Arabidopsis ( Moreau et al, 2012 ), and LST8-1 participates in adaptation to long days and hormone signaling ( Moreau et al, 2012 ; Kravchenko et al, 2015 ). In plants, the TOR complex regulates the initiation of autophagy by modulating the ATG1-ATG13 complex in response to stresses ( Mugume et al, 2020 ). There are four ATG1 isoforms and two ATG13 isoforms encoded in the Arabidopsis genome ( Huang et al, 2019b ).…”
Section: Activation Of Autophagy Through the Tor Signaling Pathwaymentioning
confidence: 99%